Analisis Tingkat Literasi Keuangan Agen Asuransi Syariah di PT. Bumiputera 1912 Medan - Aprilia, Dita; Yusrizal, Yusrizal; Syarvina, Wahyu (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine and analyze agent knowledge, agent behavior and agent attitudes towards sharia insurance at PT Bumiputera 1912 Medan. The research method used is a qualitative method used by researchers, namely primary, including distributing questionnaires to interview agents at PT Bumiputera 1912 Medan. Based on the research results obtained regarding the analysis of the level of financial literacy of Islamic insurance agents, namely, even though the knowledge level of Islamic insurance agents is in the moderate category or sufficiently understanding, the knowledge level of Islamic insurance agents should be in the understanding category. Besides that, the role of agents is also very much needed by the community, one of which is educating the public to know, know, understanding, utilize and enjoy sharia insurance services. And the level of agent knowledge, agent behavior and agent attitudes have a positive influence on Bumiputera 1912 Islamic insurance Medan. It is evident from the questionnaire distributed to the Bumiputera 1912 Medan agents, then from the results of the average velue of the level of agent knowledge and agent behavior and agent attitudes produce different values where the agent’s knowledge is lower than the agent’s behaviour and attitude of sharia insurance agents in Bumiputera 1912 Medan.